First description of the female of Ozyptila utotchkini (Araneae: Thomisidae) - Marusik, Yuri M.; Omelko, Mikhail M. (Zootaxa, 2008)
Ozyptila utotchikini Marusik in Marusik and Chevrizov (1990) was described from two male specimens from the Anuchino District of Maritime Province, Far East Russia. Since then it has also been reported from Sikhote-Alin’ Reserve (Marusik & Koponen 2001). Ozyptila utotchkini belongs to the Holarctic O. rauda-group which comprises about 10 species. The examination of both, newly collected material and specimens from museum collections from Maritime Province has uncovered the undescribed female of this species. Although collected previously, it was not known to be conspecific to the male of O. utotchkini, or a member of the O. rauda-group, as it has an unusual epigyne. Recently we recognized that O. utotchkini may represent a junior synonym of O. gasanensis Paik, 1985, known only from female holotype collected in Korea. The holotype of this species is not available (all types deposited in the private collection of K.Y. Paik were lost after his death). The goal of this paper is to describe both sexes of O. utotchkini to allow clarification of the status of the two Far Eastern species, O. gasanensis and O. utotchkini, in the future.